Combined Low-Level Light Therapy and Intense Pulsed Light Therapy for the Treatment of Dry Eye in Patients with Sjögren's Syndrome. (11th June 2021) - Di Marino, Matteo; Conigliaro, Paola; Aiello, Francesco; Valeri, Claudia; Giannini, Clarissa; Mancino, Raffaele; Modica, Stella; Nucci, Carlo; Perricone, Roberto; Cesareo, Massimo
Abstract : Purpose . To evaluate the effects of combined intense pulsed light therapy (IPL) and low-level light therapy (LLLT) in dry eye disease (DED) in patients affected by Sjögren's syndrome. Patients and Methods . This is a monocentric, prospective, interventional study. At baseline, all the study patients ( n = 20) were on tear substitute therapy and underwent Schirmer type-1 test and breakup time (BUT) test. After baseline measurements, tear substitute therapy was suspended, and patients underwent IPL and LLLT. The same investigations were carried out at one (T1) and at three (T3) months after treatment. The Ocular Surface Disease Index (OSDI) survey was used to measure the severity of DED. Results . BUT test showed an increase in tear film breakup time in patients with DED 1 month after the beginning of the treatment (T0 vs T1: p = 0, 01 ). This increase was even more statistically significant after 3 months of the IPL and LLLT treatment (T0 vs T3: p < 0.0001 ). Schirmer test values increased too, but there was not statistically significance between values at T0 and T1 or T3. The patients perceived an improvement in their condition, which resulted in a lower score on the OSDI survey. The OSDI score was lower at T1 than T0 (T0 vs T1: p = 0.0003 ), while it tended to increase again after 3 months although it was still lower than baseline (T0 vs T3: p = 0.02 ). No facial or ocular side effects were reported. Conclusions . The use of combined IPL/LLLT for the treatment of DED in patients affected by Sjögren's syndrome appears to be beneficial.